C-reactive protein (CRP) and lactate dehydrogenase (LDH) as functional outcome predictors in stroke patients - Nadhilla, Nyimas Farisa; Gofir, Abdul; Setyawan, Tommy Rachmat; Farida, Siti; Ar Rochmah, Mawaddah (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Stroke is a neurologic disorder with high mortality and disability. Its pathophysiology is associated with vascular inflammation. However, studies between vascular inflammatory markers and stroke outcomes are still limited. This study aimed to investigate the association between inflammatory markers and functional outcomes of stroke. This was a retrospective cohort study involving all stroke patients at the Dr. Sardjito General Hospital, Yogyakarta from October 2020 to August 2021 who meet the inclusion and exclusion criteria. Mann-Whitney was used for bivariate analysis, followed by multivariate analysis. A total of 269 subjects, with 213 infarcts (79.2%) and 56 hemorrhagic (20.8%) strokes. There were 83 subjects deceased (30.9%), with 66 infarct (31%) and 17 hemorrhagic (30.4%) strokes. High CRP levels had significant and independent associations with worse GCS, ADL, IADL, NIHSS, BI, SSGM, MRS, and higher mortality rates (p < 0.05). High LDH levels had a significant and independent association with worse GCS scores and higher mortality rates (p < 0.05). Sub-analysis showed high CRP and LDH had associations with high mortality rates in infarct (p < 0.001), but only CRP (p = 0.029) had associations with high mortality rates in hemorrhagic. There was no significant association between fibrinogen and procalcitonin with stroke outcomes (p > 0.05). Cox-regression analysis showed CRP>24.5 mg/dL and LDH >300U/L associated with hazard ratios of 3.2 (p < 0.001) and 1.65 (p = 0.026). In conclusion. high CRP and LDH levels are associated with mortality rates in stroke patients.